Targeted Countercyclical Capital Buffers - Sigurd Mølster Galaasen; Haakon Solheim (Norges Bank, 2018)
This paper investigates the effect of broad-based versus sectoral capital requirements using a dynamic model of bank behaviour. We study the problem facing banks when determining their dividend policy and portfolio of long-term loans to the retail and corporate sector. The return on lending is uncertain, and capital requirements may be reduced when loan losses are high, in order to stabilise lending. We find that when shifting capital between sectors is difficult or very costly, targeted regulation, such as a sectoral buffer (SCCyB), can lead to more stable lending during a crisis than a broad-based CCyB, at a lower cost. This depends on the ability of the policymaker to foresee the type of crisis. A targeted requirement is ex-post an inefficient policy if crises occur in sectors where the buffer requirement is inactive, as the targeted policy cannot effectively stabilise credit. However, the consequences of policy "mistakes" depend on the degree of sectoral segmentation in the banking market. Banks that provide credit to both the retail and the corporate sector will endogenously reallocate capital to the constrained sector in a crisis, irrespective of the kind of regulatory buffer that is implemented, thereby dampening the consequences of such inefficient policy.
hdl:11250/2578482
Keywords: 330